2021
DOI: 10.1080/00313831.2021.1910560
|View full text |Cite
|
Sign up to set email alerts
|

Registered Nurses’ Supervision of Nursing Students During Practical Skill Learning: A Qualitative Exploratory Study

Abstract: Nursing education relies on nurses to supervise students in practical skill learning during their clinical placement periods, yet literature is sparse regarding what this supervision actually entails. The study aimed to explore the learning actions that characterised nurses' and students' interaction during supervision of peripheral vein cannulation attempts on patients in hospital, and how these learning actions influenced the students' practise. In this study, 38 video-recorded attempts of the practical skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In addition to giving students opportunities to apply classroom theory to the clinical nursing field, it serves as a process of socialization that thoroughly instills expectations and habits in the students. Along with raising student accomplishment, which is still crucial in producing top-notch graduate students who will supply the nation with labor and leadership [32]. The study's findings demonstrated a highly statistically significant increase in clinical instructors' understanding of clinical supervision aspects both within the first three months following the program and beyond.…”
Section: Impact Of Clinical Supervision Program On Nursing Students' ...mentioning
confidence: 81%
See 1 more Smart Citation
“…In addition to giving students opportunities to apply classroom theory to the clinical nursing field, it serves as a process of socialization that thoroughly instills expectations and habits in the students. Along with raising student accomplishment, which is still crucial in producing top-notch graduate students who will supply the nation with labor and leadership [32]. The study's findings demonstrated a highly statistically significant increase in clinical instructors' understanding of clinical supervision aspects both within the first three months following the program and beyond.…”
Section: Impact Of Clinical Supervision Program On Nursing Students' ...mentioning
confidence: 81%
“…It also assisted clinical supervisors with the important and educational parts of the procedure. Clinical supervisors did not show any support when given the opportunity to present theoretical perspectives on the subject of meta-supervision [32].…”
Section: Discussionmentioning
confidence: 93%
“…Difficulties may arise in accessing learning situations in practice or securing patient consent. Video recording is probably a relevant method for capturing students’ actual practice ( Ravik et al., 2017a , 2017b ; Ravik and Bjørk, 2021 ), but it is laborious in terms of both data collection and data analysis. Both Lauder et al.…”
Section: Discussionmentioning
confidence: 99%
“…This study is a part of a larger study exploring practical skill learning in nursing education in the simulation-and clinical settings (Ravik et al, 2017a;Ravik et al, 2017b;Ravik and Bjørk, 2021) and transfer of skill learning from the simulation setting to the clinical setting (Ravik et al, 2015). This study had a qualitative, explorative, and comparative research design with a data-driven inductive approach that went beyond descriptions to provide the researchers with an in-depth understanding of peripheral vein cannulation skill learning (Kvale and Brinkmann, 2015;Polit and Beck, 2020).…”
Section: Designmentioning
confidence: 99%